STRUKTUR PASAR DAN ANALISIS KEUNTUNGAN KOPI ARABICA RAKYAT DI KECAMATAN SUMBER WRINGIN BONDOWOSO - Rini Purwatiningsih; Adi Ismanto (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2018)
Arabica coffee production in District Sumberwringin 2011 reached 6.08 tonnes with a productivity of 0.17 tonnes / ha. Total production and productivity is the largest number compared with other sub-districts in the regency, This study aims to: (1) find out the factors influencing the income of coffee farmers, (2) Proving the market structure formed at the level of smallholder coffee farmers is oligopsoni. Locations were selected in District Sumberwringin because it is a major production center or people's coffee-producing regency. The sampling technique using snowball sampling. The total number of samples are 30 people arabica coffee grower and 30 people robusta coffee grower. The analysis are linear regression and the concentration ratio (CR).The result in arabica coffee: the cost of drugs and labor costs have a significant effect on income, while the area of ​​land and the cost of fertilizer have no significant effect on income. The result in robusta coffee: land area and labor cost have real effect to income, while fertilizer cost and drug cost have no significant effect to income. By calculating the value of CR found more than 80 percent that the structure of the coffee market in the District Sumberwringin monopsony or oligopsony heavy concentration.